STRUCTURAL TYPES OF HYPERBOLE IN ENGLISH - Khadjieva, D.T. (FAN va JAMIYAT, 2020)
The article is an attempt in investigating the structural types of hyperbole as a stylistic device. The language material that we‘ve surveyed indicates that hyperbole is presented by a wide variety of structural types: simple, complex, single-component, multicomponential, independent and as a part of other stylistic devices. The structural types of hyperbole expressed by different parts of speech and components have been analyzed on the basis of fictional texts.